Legal Certainty of Assignment in Postponement of Debt Payment Obligations Applications: Synergy Between Positive Law, Customary Law, and the Theory of Legal Pluralism - S, Binsar Jon Vic; Iryani, Dewi; Kapanadze, Maia (Faculty of Law, Universitas Pattimura, 2026)
Introduction: The assignment of receivables through cessie is an essential instrument in Indonesian civil law practice, including within the mechanism of Postponement of Debt Payment Obligations. In practice, however, legal uncertainty often arises concerning the legal standing of substituted creditors who acquire claims through cessie when involved in Postponement of Debt Payment Obligations proceedings. The absence of explicit regulation in the Civil Code and Law Number 37 of 2004 creates juridical ambiguities that may disadvantage both creditors and debtors.Purposes of the Research: The purpose of this research is to examine the legal certainty of cessie within Postponement of Debt Payment Obligations by exploring the synergy between positive law, customary law, and legal pluralism theory.Methods of the Research: This study employs a normative juridical method, utilizing both the statute approach and the conceptual approach, with data collected through literature review of primary and secondary legal sources.Results of the Research: The findings demonstrate that legal certainty of cessie in Postponement of Debt Payment Obligations cannot rely solely on positive law but must also incorporate the legitimacy rooted in living customary law. The novelty of this research lies in the integration of legal pluralism theory to bridge positive law and customary law, thereby providing more comprehensive legal protection for both creditors and debtors. This research advances scholarly discourse by offering a model of synergy that may guide policymakers and judges in interpreting the status of cessie in Postponement of Debt Payment Obligations cases, thus ensuring legal certainty in both formal and substantive terms.